2011
DOI: 10.1007/s12070-011-0227-5
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Body Aspiration: Demographic Trends and Foreign Bodies Posing a Risk

Abstract: This study was done to find out modern demographic trends of aspiration and different foreign bodies posing a risk. For this study, 94 patients with suspected foreign body aspiration (FBA) were selected. Detailed history, especially age, suspected Foreign body (FB) and mode of onset were noted and a thorough clinical examination was done. X-ray chest and neck, antero-posterior and lateral view was the only investigation done in all. Rigid bronchoscopy under general anaesthesia was done in all the cases of susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 7 publications
0
19
0
5
Order By: Relevance
“…The whistle was found to be the most common non organic and second most common tracheobronchial FB [1]. Symptoms of a subglottic FB include cough which might subside after sometime due to fatigue and adaptation [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The whistle was found to be the most common non organic and second most common tracheobronchial FB [1]. Symptoms of a subglottic FB include cough which might subside after sometime due to fatigue and adaptation [2].…”
Section: Discussionmentioning
confidence: 99%
“…They constitute about 8% of all tracheobronchial foreign bodies [1]. Subglottic foreign bodies need urgent management as their mere presence in that area indicates their large size or adherence to the laryngotracheal wall.…”
Section: Introductionmentioning
confidence: 99%
“…Benzer şekilde YCA olan çocuklarda Mukherjee ve arkadaşları. %70.2 hastanın beş yaşın altında, Aydoğan ve arkadaşları ise 1887 çocuk hastayı kapsayan retrospektif çalışmalarında %74 hastanın üç yaşın altında olduğunu belirtmişlerdir 3,4 . Mental retardasyonu olan ve Prader-Willi Sendromu gibi aspirasyona eğilimi olan çocuklarda da YCA'nın görülme sıklığı daha yüksektir 5 .…”
Section: Trakeobronşial Sistemde Yerleşen Yabancı Cisimlere Genel Bakışunclassified
“…Tam obstrüksiyonun izlenmediği, YCA hikayesi olan çocuklarda poliklinik şartlarında total intravenöz sedasyon veya topikal anestezi altında fleksibl bronkoskopi uygulanabilmektedir 3,4,20,23 .…”
Section: Tanıunclassified
“…They constitute about 8% of all tracheobronchial FBs. 2 They need immediate removal either by rigid bronchoscopy which is the preferred method or as some studies have found, flexible bronchoscopy can also achieve a high success rate. 3 The present case is interesting to report due to the asymptomatic nature of a large whistle (subglottic) FB with a probable history of swallowing it accidently.…”
Section: Introductionmentioning
confidence: 99%